The Analysis Of Hibryd Contract Validity In The Fatwa Of The National Sharia Board Of Indonesian Ulema Council Concerning Rahn - Suprihatin, Titin (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
The DSN-MUI fatwa product concerning rahn is hibryd contract domain. In the study of fiqh muamalah mâliyyah, the use of hibryd contract has issued pros and cons due to the hadith regarding the prevention of hibryd contract transactions. This study aims to determine the construction of akad rahn in the fatwa of DSN-MUI and the hibryd contract validity in the DSN-MUI fatwa concerning rahn. This research is qualitative research with a normative juridical approach and using literature study as its data collection technique. The results indicate that the hibryd contract provisions in the DSN-MUI fatwa concerning rahn did not prohibit hibryd contract standards and limits. This is due to the provisions of mu'nah based on the akad ijârah there is no ta'aluq (relationship) between the cost of maintaining the marhȗn and the nominal of loan (akad qardh). Therefore, the concept of hibryd contract contained in the DSN-MUI fatwa concerning rahn does not issue gharar and ribâ. The implication of this research in the fiqh economic sharia framework is the development of methodology and innovation of sharia pawn products based on hibryd contract so that there is a necessity for standardization of fatwas that regulate hibryd contract in Islamic financial transactions